Revolutionary spring : Europe aflame and the fight for a new world, 1848-1849 - Clark, Christopher M. (Crown, 2023)
"As history, the uprisings of 1848 have long been overshadowed by the French Revolution of 1789 and the Russian revolutions of the early twentieth century. And yet in 1848 nearly all of Europe was aflame with conflict. Parallel political tumults spread like brush fire across the entire continent, leading to significant changes that continue to shape our world today. These battles for the future were fought with one eye kept squarely on the past: The men and women of 1848 saw the urgent challenges of their world as shaped profoundly by the past, and saw themselves as inheritors of a revolutionary tradition"--